Telaah Kritis Putusan Arbitrase Sebagai Dasar Permohonan Pailit - Harahap, Syaiful Khoiri (Jurnal Hukum & Pembangunan, 2022)
Against the arbitral award, the parties should be able to implement it voluntarily. If the losing party does not want to carry out its obligations by the specified deadline, then the obligation is a debt that must be paid by the debtor to the creditor. Based on article 8 paragraph 4, the proof in bankruptcy must be proven simply as a condition for bankruptcy of the debtor. The arbitration award should be the basis for the bankruptcy of the debtor. From the research results it can be concluded that bankruptcy can only occur if the debtor admits that he has debts to creditors and this must be proven simply. The commercial court considers the application of the arbitration award as the basis for filing a bankruptcy petition to be excessive and overlapping, resulting in the rejection of the bankruptcy petition. Therefore, judges are advised to enforce the provisions as stated in the law and be able to make legal breakthroughs (legal discoveries) in the field of bankruptcy.